Strategi Pengembangan Agribisnis Teh PT Perkebunan Tambi Kabupaten Wonosobo - Pratama, Satria Eka; Nadapdap, Hendrik Johannes (Jurnal Penelitian Pertanian Terapan, 2019)
This research aims to 1) Know the strengths and weaknesses as well as opportunities and threats of internal and external factors at Tambi Plantation, Wonosobo Regency. 2) Formulating alternative choices of tea business development strategies that can be recommended at PT Tambi Plantation, Wonosobo Regency. The implementation of this study began in February until March 2019 and the research location was at PT Perkebunan Tambi. The data analysis technique in this study uses the IFE, EFE, IE, SWOT and QSPM matrices. The results of this study are PT Perkebunan Tambi has 10 strength factors, 5 weakness factors, 7 opportunity factors and 5 threat factors faced by the company and 10 alternative development strategies are recommended for the company.